MENINGKATAN PERILAKU ANTI KORUPSI MELALUI MODEL INVESTIGATIVE REPORT: INTEGRASI MATA PELAJARAN AGAMA DAN PENDIDIKAN ANTI KORUPSI - Istiqamah; Abd. Rais Asmar (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
This study aims to improve students' anti-corruption behavior through the integration of religious education and anti-corruption education subjects. The research method uses an investigative report learning model that focuses on high school students in Gowa Regency as a sample. The investigative report learning model has proven to be successful in increasing the understanding of high school students about anti-corruption actions and behavior. Students' understanding of anti-corruption actions and behavior that initially only revolved around the government level has increased at a wider level, where students are able to identify directly in the field through investigation sheets, such as the home environment and the market environment. Some of the actions that can be identified are the act of reducing the scales, hoarding basic materials, and providing inappropriate materials. Furthermore, the role of religious teachers is also very large by providing interventions in the form of explaining the relationship between the Qur'an and the story of the Prophet Muhammad SAW to students' findings about acts that are considered acts of corruption. The final impact obtained is that students' understanding of anti-corruption actions and behavior will increase and psychologically will help students to avoid acts of corruption and spread the importance of anti-corruption behavior.